Varicella Pneumonia with Deep Venous Thrombosis and Pulmonary Embolism as Rare Presentations for Male: Case Report - Dallah, Mohammad; Hmaideh, Ahmad; Hashoom, Yaser; Kaesom, Ammaar; Gazhal, Nusima (Avicenna Journal of Medicine, 2025)
This case report presents the case of a middle-aged man who experienced a rare and severe presentation of varicella infection, with the development of varicella pneumonia and the rare complications of deep venous thrombosis, and a subsequent pulmonary embolism. Despite being immunocompetent, the patient's varicella infection resulted in an atypical and complex clinical course. The individual initially presented with a vesicopustular rash, fever, and fatigue, which progressed to severe hypoxia and dyspnea. Radiological findings revealed diffuse bilateral nodular consolidation consistent with varicella pneumonia. Although varicella pneumonia is well documented, its occurrence in immunocompetent individuals is uncommon. In the context of varicella infection, it is very rare, particularly in the absence of immunodeficiency and with no other risk factors, in a male patient. This case underscores the importance of maintaining a high index of clinical suspicion to promptly diagnose and treat potentially life-threatening complications associated with varicella infection in otherwise healthy individuals. Key learning points include the necessity of early recognition and intervention to mitigate severe complications and the potential need for thromboprophylaxis in varicella pneumonia patients and suggests the potential need for thromboprophylaxis in patients with varicella pneumonia to prevent thrombotic events.
Keywords: varicella pneumonia; deep venous thrombosis; pulmonary embolism; case report